PENGARUH PEMBERDAYAAN PEMUDA OLEH DINAS PEMUDA DAN OLAHRAGA TERHADAP PERTUMBUHAN WIRAUSAHA MUDA - Nur Susiyanti; Subur Bahri; Sri Rahayu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstract: Effect Of Youth Empowerment By The Youth And Sports Office On The Growth Of Young Enterprises (Study of Training and Advocacy by the Department of Youth and Sports In Paspan Village, Glagah District, Banyuwangi Regency) This study aims to determine the effect of training indicators (X1), advocacy (X2) on the variables of young entrepreneurship growth (Y) and the influence of youth empowerment variables by the Department of Youth and Sports (X) on the growth of young entrepreneurs. The method of data analysis in this study uses quantitative methods with data processing techniques using the Rho Spearman analysis formula. Data collected through questionnaires. The questionnaire was given to young people in Paspan Village who had received training and advocacy from the Department of Youth and Sports, which was used as a sample of the study, amounting to 16 people. Measurements are made with one to three value scales. The results obtained by the researcher indicate that the training indicators, advocacy indicators, and youth empowerment variables by the Department of Youth and Sports did affect the growth variable of young entrepreneurs. Training with a correlation of 0,543 did significantly influence the growth of young entrepreneurs. Advocacy with a correlation of 0,443 does significantly influence the growth of young entrepreneurs. The variable of youth empowerment by the Department of Youth and Sports with a correlation of 0,625 did significantly influence the growth of young entrepreneurs.